2022
DOI: 10.3390/nu14102088
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Magnesium Therapy Alleviates Moderate Stress in Patients with Fibromyalgia: A Randomized Double-Blind Clinical Trial

Abstract: Patients suffering from fibromyalgia often report stress and pain, with both often refractory to usual drug treatment. Magnesium supplementation seems to improve fibromyalgia symptoms, but the level of evidence is still poor. This study is a randomized, controlled, double-blind trial in fibromyalgia patients that compared once a day oral magnesium 100 mg (Chronomag®, magnesium chloride technology formula) to placebo, for 1 month. The primary endpoint was the level of stress on the DASS-42 scale, and secondary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 83 publications
0
8
0
1
Order By: Relevance
“…Mg has an important role in preventing central sensitization and attenuation of the pain hypersensitivity through its voltage-gated action at NMDA receptors and has been investigated for its ability to reduce acute or chronic pain in various clinical conditions ( 68 ). A recent study also reported a significant ( p = 0.003) reduction in mild/moderate stress (DASS-42 stress score) and the intensity of pain ( p = 0.029) following supplementation with oral Mg in fibromyalgia individuals ( 69 ). The important effects of the botanical extracts contained in Mg-Teadiola on brain functions have been highlighted in the previous study ( 20 ).…”
Section: Discussionmentioning
confidence: 91%
“…Mg has an important role in preventing central sensitization and attenuation of the pain hypersensitivity through its voltage-gated action at NMDA receptors and has been investigated for its ability to reduce acute or chronic pain in various clinical conditions ( 68 ). A recent study also reported a significant ( p = 0.003) reduction in mild/moderate stress (DASS-42 stress score) and the intensity of pain ( p = 0.029) following supplementation with oral Mg in fibromyalgia individuals ( 69 ). The important effects of the botanical extracts contained in Mg-Teadiola on brain functions have been highlighted in the previous study ( 20 ).…”
Section: Discussionmentioning
confidence: 91%
“…A recent study concluded that Mg intake was inversely correlated with C -reactive Protein (CRP) in the FM group [ 118 ]. Furthermore, daily supplementation of oral Mg chloride improved mild/moderate stress and reduced pain in FM patients [ 119 ]. However, larger clinical trials are required.…”
Section: Resultsmentioning
confidence: 99%
“…Followed by the generic Short Form Health Survey (SF-36), which was assessed in 44.8% of the studies. Only ten studies did apply neither the FIQ nor the SF-36 [ 32 , 69 , 73 , 82 , 83 , 98 , 99 , 105 , 109 , 128 ], although Pazzi et al and Macian et al [ 83 , 105 ] did use the 12-item Short Form of the SF-36 (i.e. SF-12).…”
Section: Resultsmentioning
confidence: 99%